Generalized Design of Columns Subjected to Combined Axial Load and Bending Moment - Monasa, Frank; Snyder, John K. (Engineering Journal, 1981)
The design of wide-flange steel columns subjected to combined axial compression load and bending moment according to the AISC Manual of Steel Construction involves a trial-and-error procedure. In this method the applied bending moment is converted to an equivalent axial load by using a bending factor. This allows the selection of a trial section from the AISC Column Tables. Then, using the modified AISC interaction formulas, the required axial tabular load can be determined. From this load, another trial section is selected, and the procedure is repeated until a satisfactory section is obtained. The selected section must be checked for compliance with the AISC Formulas (1.6-1a), (1.6-1b), and (1.6-2). This process is often tedious and time consuming and is not efficient for usage in the design office. Several methods have been presented which tend to simplify the AISC design procedure for columns subjected to combined axial load and bending moment. These methods either modify the AISC column interaction equations to minimize the number of trials used in selecting the final section, or present design charts, graphs, and tables. This paper provides a rapid selection of steel wide-flange columns subjected to combined axial compression load and bending moment about the strong axis of the member, in compliance with the AISC Specification.